Law Enforcement and Protection in The Management of Incidental Parking in Medan City - Pebri Anto Purba; M Rizal (Journal Equity of Law and Governance, 2024)
This study aims to conduct a comprehensive analysis of law enforcement and legal protection in the management of incidental parking in the city of Medan. Incidental parking refers to temporary and unscheduled parking services that are often subject to legal challenges related to governance, security, and the protection of users’ rights. Through a normative juridical approach, this study examines the level of compliance with applicable regulations, including local regulations and laws that govern parking systems in urban areas. The research also delves into the practical implementation of these regulations, identifying gaps and challenges that exist within the current system. Several key issues are highlighted, including the lack of effective supervision, inconsistencies in tariff setting, and limited transparency in the management of incidental parking services. These problems can create uncertainty and potential injustice for the public, particularly for service users who often encounter arbitrary practices. Furthermore, the study evaluates the extent to which consumer rights are protected in incidental parking scenarios, examining the legal mechanisms in place to safeguard these rights and the role of local government authorities in ensuring compliance with legal standards. The findings reveal significant weaknesses in law enforcement within the incidental parking management system in Medan, particularly in relation to regulatory oversight and enforcement. The study emphasizes the need for stronger, more effective supervision and enhanced regulatory frameworks to address existing deficiencies. In order to achieve better public protection, the local government is urged to implement policies that increase transparency, ensure fair pricing, and improve accountability among parking service providers.